Real-life validation of a sample pooling strategy for screening of hepatitis C. (January 2023) - Aguilera, Antonio; Fuentes, Ana; Cea, María; Carracedo, Raquel; Viñuela, Laura; Ordóñez, Patricia; López-Fabal, Fátima; Sáez, Elena; Cebrián, Rubén; Pérez-Revilla, Alfredo; Pereira, Sara; De Salazar, Adolfo; et al.
Abstract: Objectives: To test a real-life sample pooling screening strategy which contributes to increasing the diagnostic capacity of clinical laboratories and expanding access to massive screening of hepatitis C. Methods: After evaluating the sensitivity of the pooling strategy for seven different commercial assays which are used to determine the concentration of hepatitis C virus (HCV)-RNA in the plasma or serum, consecutive samples submitted for HCV diagnosis during the first 3 weeks of November 2021 were tested for HCV antibodies and, in parallel and in a blinded way, were pooled into 100 samples and tested for HCV-RNA. When the result was positive, a strategy to un-mask the positive(s) pool(s), which needed up to 15 total HCV-RNA tests, was used. Results: All platforms were able to detect the presence of HCV-RNA in a single sample from a patient with viremic HCV present in pools of up to at least 10 000 HCV-RNA-free samples. A total of 1700 samples (17 pools) were analysed, with an overall prevalence of anti-HCV and HCV-RNA of 0.24%. After pooling, we could detect all samples previously detected using standard diagnosis tests (reflex testing) with a specificity and sensitivity of 100% (CI, 99.78–100%). Given the median current prices of anti-HCV and HCV-RNA on the market in Spain as well as personnel costs, testing using the pooling strategy would have resulted in a save of 3320€. Conclusions: Here, we demonstrated that by improving cost effectiveness, with no loss of sensitivity and specificity, the strategy of pooling samples may serve as an appropriate tool for use in large-scale screening of HCV. Graphical abstract: Image 1